REPRESENTATIVES OF COMPANIES - Knežević, Sima (Glasnik Advokatske komore Vojvodine, 2020)
The paper deals with The content of the institute of representation and its essential meaning, and makes a comparison the solutions on represetation under the Law on Obligations, and the Law on Companies and points to different solutions. Then the term legal (statutory) representatives is processed, wich is used by the Law on Companies, and indicates the confusion that this term creates in relation to other laws, that use this term in a completely different meaning. Finally, the solutions of the Law of Companies on legal (statutory) representatives, other representatives, employment representatives and procurators are analyzed.
Keywords: representation, legal representatives, companies, employmen representatives, procurators